Raman scattering from GaAs/AlGaAs multiple quantum well structures grown by two-step molecular beam epitaxy - Lee, Taegeon; Rho, Heesuk; Song, Jin Dong; Choi, Won Jun (ELSEVIER SCIENCE BV, 2017)
We report polarized and spatially resolved Raman scattering from GaAs/Al(0.)3Ga(0.7)As multiple quantum well (MQW) structures grown by a two-temperature step molecular beam epitaxy method, in which an initial GaAs buffer layer is deposited at low temperature and a subsequent GaAs layer is deposited at high temperature. Polarized Raman spectra revealed several transverse optical (TO) and longitudinal optical (LO) phonons, i.e., GaAs, GaAs-like, and AlAs-like TO and LO phonons. The Raman peaks related to the AlGaAs barriers were significantly enhanced under resonant excitation near the band gap energy of AlGaAs, In addition, resonant Raman scattering from the side edges of the samples exhibited symmetry forbidden GaAs-like and AlAs-like LO phonons. To investigate stress and strain evolutions in the GaAs buffer layers, spatially resolved Raman measurements were performed along the growth direction, obtained via the side edges of the samples. Interestingly, Raman maps across the GaAs layers showed that the usually doubly degenerate GaAs TO phonons were split into two distinct phonons. Depending on the two-step growth temperatures, the peak energies of the TO phonons evolved differently along the growth direction. The built-in stress and strain depth-profiles in the GaAs buffer layers were estimated using a biaxial assumption. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ALXGA1-XAS; STRAINS